UKRAINIAN ELITES DISCOURSE IN RESPECT OF THE DONBASS TERRITORY AND POPULATION OF 2009-2018: ANALYSIS OF THE NATIONAL FACEBOOK SEGMENT - A. A. Tokarev (Vestnik MGIMO-Universiteta)
The conflict in the South-East Ukraine has acquired a protracted character, primarily due to the lack of consensus among key players. Ukrainian elites and society have not formed a consolidated position in relation to the Donbas. The study attempts to answer the question: what are the specifics and dynamics of the Ukrainian elites' discourse in relation to the Donbas over the past 10 years? The aim of the study is to analyze the semantics, frequency and emotionality of the two major discourses – in relation to the population and the territory of Donbas – using the analysis of the national Facebook segment. This work proceeded in several stages: from November 2016, when my colleagues and I began brainstorming, until May 2018, when the final schedules were obtained: the allocation of opinion leaders in the social network, downloading their posts from January 1, 2009 to February 15, 2018, the isolation from the discourse of posts devoted to the Donbas, the creation of a vocabulary that allows differentiating discourses according to the degree of their emotionality, an assessment of their frequency degree, an explanation of the discourses dynamics through event analysis. The database consists of 653 662 739 characters in 7 languages from 1,069,687 posts of 376 Ukrainian Facebook top-bloggers, downloaded and analyzed using the information-analytical system «Semantic Archive». The results of the analysis show that, firstly, the «birth» of discourses about both the territory and the population is the 2013-2014 boundary. Before that, the frequency of mentioning the Donbas is zero. Secondly, unlike the territory in relation to the population there is a significant negative discourse, and it has slightly increased in relative degree after 2014, but has always existed. Regarding the territory, on the contrary, the hatred discourse is absent. The neutral discourse dominates this agenda. At the very beginning of the period under review, it displaces positive discourse, showing how great is the uncertainty with regard to the territory, maintaining its relative share, beginning in January 2011. The number of positive and negative discourses in relation to the territory is a multiple of that for the population, which allows to draw conclusions about the high degree of uncertainty of elites in relation to the territory and the low probability of the transition of this neutral discourse into positive ones.